A case of late-onset larynx angioedema after ranibizumab intravitreal injection: Ranibizumab-related angioedema. (August 2020) - De Bernardo, Maddalena; Stellato, Cristiana; Rosa, Nicola; De Pascale, Ilaria; Salzano, Francesco Antonio
This case report describes an unusual case of late-onset larynx angioedema after ranibizumab intravitreal injection. A 72-year-old female patient presented to our clinic for decreased vision; right eye (RE) fundoscopy and optical coherence tomography (OCT) revealed mild chorioretinal atrophy and choroidal neovascularization with subretinal fluid. A ranibizumab injection was planned in the RE, with standard pretreatment with daily oral administration of betamethasone, cetirizine, and ranitidine because her medical history revealed two adverse drug reactions (ADRs) to contrast media (CM). Despite the premedication, 2 h after injection, the patient referred throat closing sensation and dyspnea that resolved within few hours by betamethasone 4 mg intramuscular injection, without further reoccurrence. In occasion of the second intravitreal injection, video rhinofibrolaryngoscopy revealed subglottic edema that resolved within few hours by betamethasone 4 mg intramuscular injection. This report suggests that, even in cases of intravitreal injection, patients with history of allergy, despite the anti-allergic treatment, should be hospitalized to detect late onset of such a life-threatening complication.